Simplified cascade multiphase DC-DC buck power converter for low voltage large current applications: part II — output current controller - Nungky Prameswari; Anand Bannet Ganesen; Falah Kharisma Nuraziz; Jihad Furqani; Arwindra Rizqiawan; Pekik Argo Dahono (Institute of Advanced Engineering and Science, 2021)
This paper proposes a control method for new simplified cascade multiphase direct current-direct current (DC-DC) buck power converters used for low-voltage large-current applications such as cathodic protection. To control the proposed converter, a proportional-integral (PI) controller is used to regulate the output current of the converter. The control scheme analysis is carried out by linearizing the small-signal model of the proposed converter to form the output current transfer functions. This transfer function will be analyzed by using phase and gain margin approach to obtain the control parameters (Kp, Ki, and Ti). Simulation and experiment results are included to show the validity of the proposed concept.